Dinamika Psikologis Istri Korban Perselingkuhan dalam Ikatan Pernikahan - Akmalia, Wilda; Khodijah, Uchy (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2025)
Infidelity in a husband and wife relationship is a complex phenomenon and involves a variety of issues that can affect the continuity of the marriage. In the process of infidelity, the perpetrator often experiences negative psychological impacts. Negative emotions that arise include feelings of shame, guilt, and constantly thinking about the affair (rumination). This study aims to explore the psychological dynamics of women who are victims of infidelity, especially in the aspects of cognition, emotion, and action affecting how individuals adapt and recover from painful experiences. The research used a qualitative model with a case study approach. This research involved 2 subjects who live in the Bojonegoro area as victims of their husbands who committed infidelity. The main instrument in this research is the researcher himself, the researcher as an instrument can relate directly to the respondent and is able to understand and assess various forms of interaction in the field, interviews are conducted in several stages and observation. The results of this study indicate that emotions affect behavior and decision making. Both respondents experienced intense emotions, such as anger, disappointment and hurt, but they reacted in different ways. Thus it can be concluded that differences in cognitive, emotional, and conative aspects affect how individuals deal with infidelity.